2013
DOI: 10.5977/jkasne.2013.19.4.606
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Critical Thinking Disposition on Emotional Regulation, Perceived Stress and Communication Competence among Nursing Students

Abstract: The purpose of this study was to investigate the effect of critical thinking disposition on emotional regulation, perceived stress and communication competence of students in nursing. Methods: A total of 362 students were recruited from two nursing colleges in C and S city. Data were collected by means of self reported questionnaires from December 1 to 15, 2012 and analyzed using descriptive statistics, t-test, ANOVA, Pearson correlation coefficients and multiple regression with SPSS 18.0. Results: A positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Studies have shown that dependence on Weibo (a popular social media in China) is widespread among university students in China, and such dependence is significantly passive and unintentional (Liu, 2013). A significantly negative correlation also exists between smartphone addiction and CTA (Lee and Kim, 2017). For example, some studies have reported a negative relationship between social media addiction and CTA by adopting sense of achievement and user emotions as mediating variables (Thomas, 2020).…”
Section: 3mentioning
confidence: 99%
“…Studies have shown that dependence on Weibo (a popular social media in China) is widespread among university students in China, and such dependence is significantly passive and unintentional (Liu, 2013). A significantly negative correlation also exists between smartphone addiction and CTA (Lee and Kim, 2017). For example, some studies have reported a negative relationship between social media addiction and CTA by adopting sense of achievement and user emotions as mediating variables (Thomas, 2020).…”
Section: 3mentioning
confidence: 99%